1995
DOI: 10.1021/j100026a021
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of N2 and CO as IR-Spectroscopic Probes of Acid Sites in H-ZSM-5 Zeolite

Abstract: Adsorptions of N2 and CO on H-ZSM-5 at low temperature are examined in sequence by means of transmission FT-IR spectroscopy, which enables the direct comparison of N2 and CO as probes of acid sites. Specific adsorptions of N2 and CO on Bransted acid sites (BAS) and Lewis acid sites (LAS) are distinguished by their characteristic absorption bands at 2334 (BAS) and 2351 cm-' (LAS) for N2 and at 2177 (BAS) and 2227 cm-' (LAS) for CO, respectively. Previously reported assignments of these bands are confirmed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 12 publications
3
63
0
Order By: Relevance
“…FT-IR measurement showed that the adsorption of CO led to a displacement of the frequency of the band associated to Brønsted acid sites by $320 cm À1 . This shift is the measure of acid strength of the H-ZSM-22 catalyst and it is comparable with other zeolites [30][31][32][33], see Supplementary material. From characterization results, the material presented in this contribution is phase pure and has a high surface area.…”
Section: Catalyst Characterization Resultssupporting
confidence: 71%
“…FT-IR measurement showed that the adsorption of CO led to a displacement of the frequency of the band associated to Brønsted acid sites by $320 cm À1 . This shift is the measure of acid strength of the H-ZSM-22 catalyst and it is comparable with other zeolites [30][31][32][33], see Supplementary material. From characterization results, the material presented in this contribution is phase pure and has a high surface area.…”
Section: Catalyst Characterization Resultssupporting
confidence: 71%
“…It was suggested that CO extinction coefficient is diminished upon adsorption on Lewis sites. [44] Therefore, even if the intensity of the signal may seem negligible compared with other signal in the spectrum, it might not have a direct implication on the actual quantity of Lewis sites.…”
Section: Resultsmentioning
confidence: 99%
“…This results in a reduced contribution of anti-bonding character to the C-O bond, making the bond stronger. This is observed as a large blue shift of the C-O stretching IR band [37,38], as illustrated in figure 5 [39]. When CO is adsorbed on Bro¨nsted acid sites, a red shift of the stretching band of the acidic OH band is observed with a small blue shift of the C-O stretching band.…”
Section: Distinction Of Acid-typementioning
confidence: 84%
“…This is in accord with a decrease in the symmetry of the molecule in the adsorption state. When N 2 is adsorbed on Lewis acid sites, a large blue shift of the N-N stretching band is observed as well as the case of CO [37,38]. Therefore, N 2 can be also used as a probe molecule for characterizing the properties of surfaces…”
Section: Distinction Of Acid-typementioning
confidence: 98%